Examining a Group Acceptance and Commitment Therapy Intervention for Music Performance Anxiety in Student Vocalists - Clarke, Laura K.; Osborne, Margaret S.; Baranoff, John A. (Frontiers in Psychology, 2020)
Music performance anxiety (MPA) is a distressing and persistent anxious apprehension related to musical performance. The experience of MPA forces many musicians to give up performing or develop maladaptive coping mechanisms (e.g., avoidance or substance use), which can impact their career and wellbeing. High levels of MPA in students and vocalists are reported in the literature. Vocalists present a unique challenge for clinicians in that vocal and breathing mechanisms, required for performance, are negatively impacted when anxious. Acceptance and Commitment Therapy (ACT) has demonstrated efficacy for the treatment of a range of psychological problems including Social Anxiety Disorder (of which MPA may be indicated as a subtype). This study sought to investigate whether group-based ACT may be a feasible and effective intervention for MPA in Australian student vocalists and aimed to design an intervention that could be adopted by music education providers. Potential participants (N = 31) completed an online survey including demographic questions and outcome measures. Six vocal students (4 females; 2 males; aged M = 20.33 years) with elevated MPA scores participated in the ACT for MPA group program and 3-month follow-up. Group sessions were 2 hours each week for 6 consecutive weeks. Participants were followed up 3 months post-intervention via online survey. There was a significant increase in psychology flexibility and significant decreases in MPA and psychological inflexibility. Gains were maintained at 3-month follow-up. The current study offers preliminary evidence for the feasibility and effectiveness of a group-based ACT protocol for musicians with performance anxiety which may be incorporated into tertiary performance training curricula.